2011
DOI: 10.1007/s11739-011-0654-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a structured physical activity intervention on measures of physical performance in frail elderly patients after cardiac rehabilitation: a pilot study with 1-year follow-up

Abstract: The objective of this prospective randomized controlled study was to compare the long-term effects of a structured physical activity intervention with those of aerobic exercises alone, in a cohort of elderly patients who had undergone elective cardiac surgery, and who were classified as frail at the end of rehabilitation based on their Short Physical Performance Battery (SPPB) score. At the end of rehabilitation, 140 frail elderly patients were randomly allocated either to the intervention group (IG) or to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
3
29
1
Order By: Relevance
“…The aims of this restriction are to promote sternal osteosynthesis and bone healing by minimising motion between the sternal edges [8, 15, 63]. However, the effect of sternal precautions on patient outcomes is unknown, with significant variation among institutions worldwide [8, 13, 14, 26]. In addition, there is limited evidence to support their widespread application in clinical practice [8, 13, 15, 18, 62, 64, 65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of this restriction are to promote sternal osteosynthesis and bone healing by minimising motion between the sternal edges [8, 15, 63]. However, the effect of sternal precautions on patient outcomes is unknown, with significant variation among institutions worldwide [8, 13, 14, 26]. In addition, there is limited evidence to support their widespread application in clinical practice [8, 13, 15, 18, 62, 64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…The Short Physical Performance Battery (SPPB) is a functional test that measures daily functional activities in the acute care in-patient older population, including cardiac surgery [26]. The test is a well-established and validated measure of lower extremity performance and is designed to simulate routine physical activities in older adults [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found no change in SPPB following 1.6 years of a maintenance exercise program 16 while another resulted in improvements at 1 year in elderly frail patients who incorporated strength, flexibility, balance, and coordination exercises in addition to aerobic exercise. 17 …”
Section: Introductionmentioning
confidence: 99%
“…It is important to evaluate effective, low-impact, and enjoyable physical activity strategies for older persons, to prevent frailty and loss of independence. It has been suggested that any exercise intervention that improves the SPPB score might delay the occurrence of movement disability in elderly individuals 25,26. To date, no scientific data exist on the efficacy of FDMS training with the Wun-Jo device.…”
Section: Introductionmentioning
confidence: 99%